HUBUNGAN ANTARA MOTIVASI KERJA DAN KEMAMPUAN MENGELOLA PEMBELAJARAN IPS DENGAN KINERJA GURU - Yusnina Yusnina (JURNAL SOCIUS, 2013)
To build quality human resources, the role of education is one very important factor. Educational success is determined by several factors many of which are internal factors and external factors. The ability of teachers to manage teaching and learning can encourage students to develop their potential. Therefore, the attention of all parties on improving teachers' motivation and ability which in turn will affect the performance of teachers is crucial in improving the quality of education in schools. By using multiple linear regression models in this study was identified that motivation has a very dominant role in the improvement of teacher performance factors other than teacher ability. If the motivation of teachers and the variable ability of teachers to manage classroom teaching contributes significantly to the performance of teachers, then it should be the principal and related educational agencies and teachers to give serious attention to these variables.Keywords: Motivation, Ability, and Teacher Performance.